Dari Istana Salomo ke Ruang Kelas Kristen: Pedagogi Hikmat sebagai Model Pembentukan Etos Pelayanan dan Karakter - Ferdinan Pasaribu; Yunema Lase (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2026)
This study explores the theological meaning of the pedagogy of wisdom in the story of Solomon’s servants (1 Kings 10:1–13) as a model for developing service ethos and character in contemporary Christian education. Using a qualitative-descriptive method through theological hermeneutics, the research reveals that Solomon’s wisdom is not merely intellectual but relational and transfigurative, guiding humans into participation in the glory of God. The servants were praised not for external splendor but for their embodiment of divine wisdom through character and service. The findings propose a new paradigm in Christian education: shifting from a cognitive orientation to spiritual formation grounded in the theology of theosis. Thus, the Christian classroom becomes a space of transfiguration where both educators and learners grow together in the wisdom and character of Christ. This study highlights the importance of integrating theological dimensions into educational praxis so that character formation moves beyond morality toward divine participation.